Screening and Prostate-Cancer Mortality in a Randomized European Study - Schröder, Fritz H; Hugosson, Jonas; Roobol, Monique J; Tammela, Teuvo L.J; Ciatto, Stefano; Nelen, Vera; Kwiatkowski, Maciej; Lujan, Marcos; Lilja, Hans; Zappa, Marco; Denis, Louis J; Recker, Franz; et al. (The New England journal of medicine, 2009)
In this trial, investigators tested the effect of prostate-specific–antigen testing on the death rate from prostate cancer in more than 162,000 men between the ages of 55 and 69 years in seven European countries. A significant reduction in prostate-cancer mortality was found after a median follow-up of 9 years. Overdiagnosis and overtreatment were important limitations of the screening program. Measurement of serum prostate-specific antigen (PSA), a biomarker for prostate cancer, 1 is useful for the detection of early prostate cancer. 2 Nevertheless, the effect of PSA-based screening on prostate-cancer mortality remains unclear. 3 The European Randomized Study of Screening for Prostate Cancer (ERSPC) was initiated in the early 1990s to determine whether a reduction of 25% in prostate-cancer mortality could be achieved by PSA-based screening. 4 Preliminary data from this study have been published and can be accessed at www.erspc.org. Another randomized screening trial in the United States, the Prostate, Lung, Colon, and Ovarian (PLCO) Cancer Screening Trial, was initiated around the same . . .